Assessment of Lean Construction Practice at Selected Construction Sites in Klang Valley - Ahmed, Mohammed Elhaj Alsoufi Mohammed; Wong, Leong Sing (International Journal of Engineering and Technology, 2018)
Lean construction is known to reduce costs, improve profit or increase competitiveness, increase business opportunity and customer base, improve health and safety, improve quality, yield higher employee salaries, shorten production timescales and increase customer satisfaction. With little attention on research of lean construction in Malaysia, it remains a problem of non-standardization in waste elimination strategies thereby sub optimizing waste management in Malaysian construction projects. The objective of this paper is to evaluate lean construction techniques and measure the feasibility in term of their applicability for construction at selected sites in Klang Valley, Malaysia. The study is novel and significant in a sense that it can help to develop reliable management strategies for implementing lean construction technologies at the construction sites. Case studies were carried out as a strategic method and comprehensive survey that covers both questionnaire and interview were adopted as a method of data collection. Likert scale 1 to 5 was used in the written questionnaire with workers in order to assess the level of awareness and acceptance on the need of lean construction techniques for eight construction sites in various places and with various categories (infrastructure and building construction projects) in Klang Valley, Malaysia. Later, semi structural interview was conducted with expert judgment to justify the factors which affect the implementation of lean construction at the construction sites. From the study outcome, it was discovered that both Total Quality Management (TQM) and Industrialized Building System (IBS) were rated by the respondents to be highly effective in both infrastructure and building construction projects.
Keywords: Lean construction; Strategic method; Questionnaire; Interview; Expert judgment